An integration of theories to identify the factors enabling strategic technology alliances - Jabar, Juhaini; Soosay, Claudine (2009)
Organisations are realising the strategic importance of technology alliances to enhance their competitiveness. Today’s business environment compels firms to adopt appropriate technologies for effective and efficient operations. While many firms are inclined to source external technology or form alliances, there are various considerations that can affect the success of such initiatives. This study will focus on the relationship between factors enabling strategic technology alliances (STAs) and organisational performance. Based on four theories namely: Resource-based View (RbV); Transaction Cost Economics (TCE); Organisational Learning Theory (OLT); and Diffusion of Innovations (DoI), this paper presents a model on strategic technology alliance (STA) with specific focus on the factors enabling STA, that will eventually lead to positive organisational performance. The model then enables several empirically testable propositions that are relevant to develop a survey instrument for this study.